2012
DOI: 10.3113/fai.2012.1145
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Foot and Ankle Outcome Score for Hallux Valgus

Abstract: Patient-based assessments have become increasingly important in evaluating treatment effectiveness. This study has shown that the FAOS has acceptable construct validity, reliability, and responsiveness in hallux valgus patients and is a useful patient-based tool in assessing these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
105
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(120 citation statements)
references
References 25 publications
11
105
1
1
Order By: Relevance
“…In our assessment of the content validity, or relevance, of the FAOS from the patient's perspective, we found that the FAOS was deemed relevant in all subscales with the exception of ADLs. Though the ADL subscale showed a trend toward relevance with a preoperative and postoperative average of 1.9, this finding is consistent with those found in recent FAOS validation studies for hallux valgus and flatfoot deformity [5,11]. Though it is, however, important to note that in the validation of Roos et al of the FAOS for ankle ligament reconstruction all subscales were deemed relevant [18].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our assessment of the content validity, or relevance, of the FAOS from the patient's perspective, we found that the FAOS was deemed relevant in all subscales with the exception of ADLs. Though the ADL subscale showed a trend toward relevance with a preoperative and postoperative average of 1.9, this finding is consistent with those found in recent FAOS validation studies for hallux valgus and flatfoot deformity [5,11]. Though it is, however, important to note that in the validation of Roos et al of the FAOS for ankle ligament reconstruction all subscales were deemed relevant [18].…”
Section: Discussionsupporting
confidence: 86%
“…This broad range does carry a concern regarding the ability of the FAOS to provide consistent assessment in both the immediate and long term. However, this concern is tempered by our reliability findings being consistent with those proven for the FAOS validation for both hallux valgus and flatfoot deformity with each also found the FAOS reliable on all subscales [5,11].…”
Section: Discussionsupporting
confidence: 85%
“…Another thing to consider is improving the frequency of reporting sport-specific subscales of already validated questionnaires. The AOFAS[35], FAOS[59,153,154] and Thermann[43] scores include sports and activity sub-scales but these subscales are infrequently reported. Finally, though all terms implying sports participation of activity were included in this systematic review, it was noted that a number of different terms were used in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…However, the sports and recreation subscale of the FAOS showed little responsiveness to hallux valgus surgery. Ceiling effects were present for the ADL and sports subscale [45]. Data on MCID could not be traced [ Table 1].…”
Section: Disease-specific Outcome Measuresmentioning
confidence: 99%
“…It has been validated in the original manuscript, on patients after ankle ligament reconstruction. Recently it has been validated for patients with hallux valgus, showing acceptable reliability and responsiveness [45,46]. However, the sports and recreation subscale of the FAOS showed little responsiveness to hallux valgus surgery.…”
Section: Disease-specific Outcome Measuresmentioning
confidence: 99%